Proceedings of the 22nd International Conference on Industrial Engineering and Engineering Management 2015 Core Theory and Applications of Industrial Engineering (Volume 1) - Qi, Ershi; Shen, Jiang; Dou, Runliang (Atlantis Press : Imprint: Atlantis Press, 2016)
Being the premier forum for the presentation of new advances and research results in the fields of Industrial Engineering, IEEM 2015 aims to provide a high-level international forum for experts, scholars and entrepreneurs at home and abroad to present the recent advances, new techniques and applications face and face, to promote discussion and interaction among academics, researchers and professionals to promote the developments and applications of the related theories and technologies in universities and enterprises, and to establish business or research relations to find global partners for future collaboration in the field of Industrial Engineering. All the goals of the international conference are to fulfill the mission of the series conference which is to review, exchange, summarize and promote the latest achievements in the field of industrial engineering and engineering management over the past year, and to propose prospects and vision for the further development. This volume is the first of the two proceedings volumes from this conference.